Distribuição espaço-temporal e dinâmica populacional do Siri Callinectes Danae Smith, 1869 (Decapoda: Portunidae) na região adjacente à Baía de Babitonga, Santa Catarina - Sabino, Filipe Nathan Assunção [UNESP] (2014)
Studies on the distribution of marine organisms are essential for obtaining information on regions affected by human activities and for the understanding of the population dynamics of species. Thus, the present study aimed to investigate the abundance, spatial-temporal distribution and population dynamics of the crab Callinectes danae in adjacent region of the Babitonga Bay. Biological and abiotic samples were obtained monthly in the region from July/2010 until June/2011. Samples were collected at 5, 8, 11, 14 and 17m deep, using a fishing boat equipped with doble -rig nets. The number of individuals and the following abiotic factors were recorded at each depth: salinity and bottom temperature, organic matter and sediment texture. A total of 3,999 individuals were collected, with difference between the numbers of males (229) and females (3770). The individuals were measured concerning the carapace width (CW) and classified according to the development stage. The estimated value where 50 % of individuals were able to reproduce was 75.2 mm (CW) for males and 62.9 mm (CW) for females. The value of L ∞ for the growth analysis was fixed based on literature values, where males and females showed the asymptotic width of 102.01 and 84.41 respectively, the growth constants of 0.007 and 0.006/day, as well as the longevity of 633 and 702 days. Prevalence of female in larger size classes may be associated with characteristics of this species, which individuals migrate to different regions depending on the life stage. Reproductive females search for areas with higher salinity, while juvenile and males preferably live in estuarine areas, corroborating with is found in the current literature. Reproduction was continuous showing that the sampled area has a primordial importance for the perpetuation of this species, since it shelters a very high percentage of reproductive females. The information from this study...